Ecofeminism - Mies, Maria; Shiva, Vandana (London ; Jaipur ; New Delhi : Zed Books, Rawat Publications, 2014)
Should women see a relationship between patriarchal oppression and the destruction of Nature in the name of profit and progress? How can they counter the violence inherent in these processes? Should they look to a link between the women's movement and other social movements? The authors offer an analysis of such issues from a unique North-South perspective. They critique prevailing economic theories, conventional concepts of women's emancipation, the myth of 'catching up' development, the philosophical foundations of modern science and technology, and the omission of ethics when discussing so many questions including advances in reproductive technology. In constructing their own ecofeminist epistemology and methodology, they look at movements advocating consumer liberation, subsistence production and sustainability , and argue for an acceptance of limits and reciprocity and the endless commoditification of needs.-- From publisher's description.
Includes bibliographical references and index.
Keywords: Ecofeminism; Human ecology; Economic development -- Social aspects